2013
DOI: 10.1080/00103624.2013.803566
|View full text |Cite
|
Sign up to set email alerts
|

Short-Time Response of Microbial Communities to Waste Compost Amendment of an Intensive Cultivated Soil in Southern Italy

Abstract: In an intensely cultivated soil in southern Italy, the effects of municipal waste compost on soil activities (basal respiration, β-glucosidase, and fluorescein diacetate (FDA) hydrolysis), Biolog functional diversity, pH, and electrical conductivity (EC) were estimated in a short period following amendment. Treatment with compost at 30 t ha −1 (dry matter) was compared to mineral fertilization and untreated soil. In these poor soils, organic amendment allowed the rapid recovery of an active and biodiverse soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…The respiration rate reflects the instantaneous microbial activation induced by labile-C compounds [30]. In this study, the BR pattern was similar to those described previously by Pane et al [26] and Cytrin et al [32] with an initial burst of activity induced by compost, followed by a significant decrease approaching levels of the notamended soil. In fact, fluorescein degradation due to generalist enzymes, such as proteases, lipases and esterases [33], β-glucosidase and dehydrogenase, exhibited time-shifted trends.…”
Section: Effects Of On-farm Compost On Soil Biological Activitiessupporting
confidence: 74%
See 2 more Smart Citations
“…The respiration rate reflects the instantaneous microbial activation induced by labile-C compounds [30]. In this study, the BR pattern was similar to those described previously by Pane et al [26] and Cytrin et al [32] with an initial burst of activity induced by compost, followed by a significant decrease approaching levels of the notamended soil. In fact, fluorescein degradation due to generalist enzymes, such as proteases, lipases and esterases [33], β-glucosidase and dehydrogenase, exhibited time-shifted trends.…”
Section: Effects Of On-farm Compost On Soil Biological Activitiessupporting
confidence: 74%
“…These findings suggest that the nutritional value alone cannot totally explain the agronomic performances of the composts. But, other factors, such as the absence of phytotoxicity [25], the activation of soil useful microorganisms [26] or disease suppressiveness mechanisms, improvement of soil physical propriety, should be totally considered. Remarkable reduction in crop yield under plant stress due to phytotoxic composts has been widely reported [27].…”
Section: Effects Of On-farm Compost On Plant Growth and Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The degradation of organic matter results in the release of CO 2 from H 2 O and heat, as well as the production of nutrients. Compost contains a high level of plant nutrients with beneficial effects on the physicochemical and biological soil properties [ 154 ]. The production of composts from vegetable residues has known for years.…”
Section: Tpw Ppw and Bpw Valorisation Methodsmentioning
confidence: 99%
“…Compost is the final product of the composting process, a solid state controlled microbial fermentation of organic and no degraded matters, which can include crop residues, animal wastes, food garbage, organic municipal and industrial wastes. Pane et al [1] reported the beneficial effects of agricultural utilization of compost on physical, chemical, biochemical and biological properties of the soils. In the last years, the development of new products derived from compost, such as compost teas (CTs) is increasing, due to their positive effects on the crops [2].…”
Section: Introductionmentioning
confidence: 99%